Complex facial reconstruction based on 3D-models: prelamination cases and literature revision - Ana Francisca dos Santos Frias Correia (2020)
Background: There is little literature recalling the combined use of 3D-modeling and prelamination, but the use of 3D-models in the planning of surgeries using free flaps has been vastly described. The purpose of the present study was to also demonstrate the applicability of the combined use of 3D-models and prelaminated free flaps in the correction of complex facial deformities. Methods: A literature revision was performed in order to find the current applicability of 3D-modeling combined with free flaps and which free flaps were most commonly used in these cases. We also selected two patients with significant facial disfiguration that were submitted to surgeries that included prelamination and 3D-modeling and presented their outcomes. Results: 3D-modeling is mostly used in the correction of mandibular defects with fibular free flaps. Here we demonstrated the importance of 3D-modeling in surgeries using different types of free flap - prelaminated ones. The two patients selected achieved an aesthetic and morphological improvement that would hardly be obtainable otherwise. Conclusion: Prelamination used alongside 3D-modeling can be a powerful tool in the correction of diverse facial deformities.